MORAL EDUCATION IN A CHANGING WORLD: CHALLENGES AND SOLUTIONS - Adeola, Kehinde Oluwaseun; Olatunji , Abiola (International Research Journal of Arts and Communication, 2024)
This paper examines the role of Social Studies in the teaching of morals to minimize the prevalence of moral degeneration in contemporary Nigerian society. The causes and consequences of moral degeneration in society were examined. The paper employed the descriptive survey research design and Social Learning Theory to explain that individuals tend to act based on their observations in society. The paper made use of both primary (questionnaire) and secondary (books, journals, and online materials) types of data. The paper was guided by three research questions. The findings revealed that social studies being a value and moral-laden subject can help minimize moral degeneration's prevalence in contemporary Nigerian society. It is recommended that there should be a national re-orientation of national values among Nigerians by Nigeria's federal, state, and local governments.